2018
DOI: 10.2147/ijwh.s149683
|View full text |Cite
|
Sign up to set email alerts
|

Aplastic anemia during pregnancy: a review of obstetric and anesthetic considerations

Abstract: Aplastic anemia is a hematologic condition occasionally presenting during pregnancy. This pathological process is associated with significant maternal and neonatal morbidity and mortality. Obstetric and anesthetic management is challenging, and treatment requires a coordinated effort by an interdisciplinary team, in order to provide safe care to these patients. In this review, we describe the current state of the literature as it applies to the complexity of aplastic anemia in pregnancy, focusing on pathophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 91 publications
0
20
0
Order By: Relevance
“…This was caused by maternal factors which was aplastic anemia. 10,11 Cesarean in our case was indicated due to fetal IUGR although in cases of aplastic anemia, vaginal birth is preferred. As recommended to this patient we make sure that the platelet count was >20x103/μL which acceptable for vaginal delivery and 50x103/μL for cesarean delivery.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…This was caused by maternal factors which was aplastic anemia. 10,11 Cesarean in our case was indicated due to fetal IUGR although in cases of aplastic anemia, vaginal birth is preferred. As recommended to this patient we make sure that the platelet count was >20x103/μL which acceptable for vaginal delivery and 50x103/μL for cesarean delivery.…”
Section: Discussionmentioning
confidence: 81%
“…Intrauterine growth retardation complicated as one of our cases. 4,[9][10][11] Fetal growth surveillance should be performed by 28 weeks of gestation, and antenatal testing should also be offered by 30-32 weeks, due to the high prevalence of growth restriction. In this case, growth restriction was identifi ed after close monitoring and established by abdominal circumference and estimated fetal weight in 31 weeks gestational age correspond to 1500 g. The asymmetrical IUGR fi nding from the ratio head and abdominal circumference (>1.2) indicated new-onset hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than postpartum hemorrhage, there are no known obstetrical complications that are specific to pregnancy in women with aplastic anemia. Remarkably, however, previous studies have reported that the rate of pregnancy complications in women with aplastic anemia, including preeclampsia, fetal growth restriction, and preterm delivery, were variable [8,17,18]. Interestingly, infarction in the placenta without fetal growth restriction has been reported previously in cases of ITP that were treated with the thrombopoietin receptor agonist romiplostim during pregnancy [19].…”
Section: Discussionmentioning
confidence: 90%
“…In some cases, women with aplastic anemia experience worsening symptoms or relapse during pregnancy [1,2], and marked thrombocytopenia is often observed with advancing gestation. However, available treatment options during pregnancy are limited; hematopoietic stem-cell transplantation or the use of ATG is generally contraindicated in pregnancy [1,8], and only cyclosporin, whether it is effective or not, is thought to be safe. Ultimately, supportive care with blood products is the mainstay of treatment of aplastic anemia in pregnancy.…”
Section: Discussionmentioning
confidence: 99%